An economic assessment of options for operating within plantation forestry water entitlements and tightening cap and trade policy. (23rd February 2023) - Regan, Courtney M.; Connor, Jeffery D.; Iftekhar, Md Sayed
Abstract: The Green Triangle (GT) region of southern Australia is one of only two jurisdictions globally to licence plantation forestry's groundwater use. In response to declines in groundwater resources caused by historical plantation expansion, reductions in forest water allocations (~50%) are likely for some parts of the region, presenting novel challenges for forest managers in maintaining revenues and timber flows. This article presents a mathematical programming model evaluation of water trade opportunities for plantation forest owners to adapt to reduced water entitlements and explores how tightening groundwater policy could affect forestry returns and land use mix for the region. Results suggest that even absent opportunity to sell water, relatively limited 11% reduction in return could be expected for a large (−50%) water entitlement and (−48%) land‐use change out of forestry. Results suggest that opportunities for forestry companies to sell water entitlements may allow them to maintain or even increase combined returns from forestry and water sales. Whilst the results highlight the adaptive capacity of the plantation forestry sector to operate within reduced water entitlement, a significant sectoral and regional economy adjustment would be likely. The discussion focusses on the potential to realise optimisation model‐identified adaptation opportunities accounting for real‐world thin markets, transaction costs and market friction.